2020
DOI: 10.1039/d0nj00474j
|View full text |Cite
|
Sign up to set email alerts
|

Spin-crossover in iron(ii) coordination compounds with 2,6-bis(benzimidazol-2-yl)pyridine

Abstract: Novel iron(ii) bromide, nitrate and dicyanamide complexes with 2,6-bis(benzimidazol-2-yl)pyridine possessing high-temperature 1A1 ↔ 5T2 spin crossover were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The nickel(II) ion shows a distorted octahedral coordination environment defined by two bbp ligands, with two trifluoromethanesulfonate ions and a diethyl ether molecule in the outer coordination sphere. All the Ni-N bond lengths are in good agreement with comparable nickel(II) bbp complexes currently available in the Cambridge Structural Database (CSD, version 5.45, Nov 2023; Groom et al, 2016;refcodes BEQTAV;Harvey et al, 2018;DURWUJ;Huang et al, 2010;MUNDAD;Ivanova et al, 2020;ZOTVIP;Wei et al, 2015;KUPFUZ;Icsel et al, 2020b), The N-Ni-N angles also concur with the values reported in the previously referenced nickel(II) bbp complexes. All relevant bonds and angles are presented in Table 1.…”
Section: Structure Descriptionsupporting
confidence: 85%
“…The nickel(II) ion shows a distorted octahedral coordination environment defined by two bbp ligands, with two trifluoromethanesulfonate ions and a diethyl ether molecule in the outer coordination sphere. All the Ni-N bond lengths are in good agreement with comparable nickel(II) bbp complexes currently available in the Cambridge Structural Database (CSD, version 5.45, Nov 2023; Groom et al, 2016;refcodes BEQTAV;Harvey et al, 2018;DURWUJ;Huang et al, 2010;MUNDAD;Ivanova et al, 2020;ZOTVIP;Wei et al, 2015;KUPFUZ;Icsel et al, 2020b), The N-Ni-N angles also concur with the values reported in the previously referenced nickel(II) bbp complexes. All relevant bonds and angles are presented in Table 1.…”
Section: Structure Descriptionsupporting
confidence: 85%
“…The ligand molecule L has only a slight deviation from planarity: the angle of inclination of the root-mean-square planes of the imidazole fragments with respect to the plane of the pyramidal fragment does not exceed 1 • , and the methyl group is deviated by only 4 • . The coordination polyhedron of copper(II) is completed into a tetragonal pyramid due to two chloride ions (d Cu-Cl is equal to 2.2137 (11) Å in the equatorial plane and 2.6761 (11) Å in the axial position). Additionally, the structure is stabilized by stacking interactions between the two nearly planar organic ligands of adjacent molecules with the shift in the equatorial plane and the mean-square distance between the square pyramidal bases of about 3.42(8) Å.…”
Section: X-ray Structure Determinationmentioning
confidence: 99%
“…Both the literature data [ 9 ], and the results of X-ray and EXAFS spectroscopy obtained by us show that ligands of this class are coordinated to iron(II) in a tridentate-cyclic (pincer) type by an N atom of pyridine and two N(3) atoms of imidazole cycles. For most of the studied iron(II) complexes with 2,6-bis(1 H -imidazol-2-yl)pyridine derivatives, a high-temperature one- or two-stage SCO 1 A 1 5 T 2 is observed [ 10 , 11 , 12 , 13 , 14 , 15 ]. In contrast to the iron(II) complexes with 1,2,4-triazoles and tris(pyrazol-1-yl)methanes previously studied by us [ 5 , 16 , 17 ], we have not observed the phenomenon of thermochromism in a series of Fe(II) compounds with 2,6-bis(1 H -imidazol-2-yl)pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…(1H-imidazole-2-yl)pyridines [21]. We earlier reported a number of works devoted to the study of iron(II) complexes with 2,6-bis(1H-imidazole-2-yl)pyridine derivatives (Scheme 1) exhibiting the 1 A 1 $ 5 T 2 spin crossover [22][23][24][25][26][27].…”
mentioning
confidence: 99%